The Relationship Between Corporate Social Responsibility (CSR) and Malaysia Halal Industry - Mohd Rafiq Abdul Rahim (USIM Press, 2024)
Vol. 23 No. 1 (2020): Journal of Islamic Social Sciences and Humanities